Single-cell studies on hapten-specific B cells: response to T-cell-dependent antigens. - Hebbard, G S (1984)
The effectiveness of the hapten-gelatin antigen-affinity fractionation technique for selection of hapten-specific B cells activatable by "T-cell-dependent" (TD) stimuli was assessed. Normal adult murine spleen cells were fractionated on fluorescein (Flu)-gelatin layers and the adherent cells were cultured singly or in small numbers with various sources of syngeneic keyhole limpet hemocyanin (KLH)-primed T lymphocytes. Conditions were defined under which the addition of Flu-KLH caused optimal clonal proliferation and differentiation of B cells into anti-Flu directly hemolytic plaque-forming cells (pfc). It was found that 3-5% of the Flu-specific B cells could be activated, versus 1 in 5000 unfractionated spleen cells. The mean enrichment factor for fractionation was 179, almost identical to that seen when the stimulus is "T-cell-independent" (TI), showing that the method is capable of isolating B cells responsive to antigenic stimuli requiring specific T-cell help. Efforts were made to determine whether TD B cells constituted a separate population from TI B cells by determining clone frequencies using Flu-KLH, the TI antigen Flu-polymerized flagellin (Flu-POL), or a mixture of both for stimulation. With Flu-POL alone and with the mixed stimulus 2-3 times more pfc clones were produced than with Flu-KLH, yet evidence for separate B-cell subsets was not obtained because of strong "bystander" stimulation due to the presence of the carrier-primed T cells in a confined volume of 10 microliters.